Camouflaging in an everyday social context: An interpersonal recall study. (July 2021) - Cook, Julia; Crane, Laura; Bourne, Laura; Hull, Laura; Mandy, William
Camouflaging is a social phenomenon operating within everyday social interactions of autistic and non-autistic people. The current study explored autistic adults' camouflaging in an everyday social context via interpersonal process recall methodology (Kegan, 1969). A total of 17 autistic adults (8 females, 6 males and 3 agender/gender-neutral individuals) participated in a 10-min controlled social task designed to replicate a common day-to-day social situation. Participants then watched a video of their interaction with a researcher, actively identifying instances of camouflaging and discussing their experiences of camouflaging. Using thematic analysis, four themes were generated: (1) a strong desire for, yet uncertainty in, securing social acceptance and connection; (2) camouflaging, developed over time, as a means to achieve social acceptance and connection; (3) experiencing intrapersonal and interpersonal camouflaging consequences during social interactions; and (4) authentic socialising as an alternative to camouflaging. These findings are discussed with reference to the existing literature on stigma management outside the field of autism. Lay abstract: Many autistic people report that, despite personal costs, they use strategies to hide their autistic characteristics or appear non-autistic at work, school or university, when speaking with health professionals, or while socialising with certain friends and family members. These strategies are often referred to as camouflaging. This study explores camouflaging during everyday social interactions. A total of 17 autistic adults were filmed taking part in a common everyday social situation – a conversation with a stranger. They then watched the video of this conversation with a researcher and answered questions about camouflaging. These autistic people told us that they (1) had a strong desire to socialise with and be valued by other people but, because of negative past experiences, they often felt unsure about their ability to do so; (2) used camouflaging to help them to socialise and be valued by others; (3) experienced negative consequences when camouflaging (e.g. fatigue, anxiety and difficulties in friendships); and (4) sometimes socialised in more autistic ways instead of camouflaging. This study shows us how autistic people often change their behaviour because of the way they are treated by nonautistic people and that autistic people may benefit from programmes that help them to socialise in more authentically autistic ways, but only if their autistic social behaviour is met with understanding and acceptance from non-autistic people.